DAMPAK IMPLEMENTASI KEBIJAKAN PEMERINTAH JEPANG TERHADAP DEKLARASI UNITED NATIONS DECLARATION ON THE RIGHTS OF INDIGENOUS PEOPLES (UNDRIP) STUDI KASUS MASYARAKAT AINU - Satrio Syahreza; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted to look at the process of how a country, in this case Japan, implements international policies that have been ratified into state laws and the impact after these policies are implemented. The implementation of this policy is related to the rights of indigenous peoples in Japan, in this case the Ainu People. Research is based on decision making theory, the level of analysts used in this study is to use the level of analysis of the State. The Japanese government which ratified and implemented international declarations on people's rights and customs into the laws of the country. Data collection is by library study which conducts library reviews to libraries and collects several books, reference materials from written journals and other references relevant to United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) policy implementation in Japan. The paper show that the implementation of the UNDRIP in Japan had an impact on the Ainu People, namely with the presence of the New Ainu Law, which obliges the Japanese government to adopt policies in steps to prohibit discrimination against the Ainu people and facilitated people's understanding of Ainu traditions and the importance of diversity contributed by ethnic groups to society, in this case the Japanese government launched Upopoy National Ainu Museum and Park as part of the cultural preservation program of the Ainu People. Keywords: UNDRIP, Policy Implementation, Ainu People